The effect of PreAcid BA® on the performance and health status of growing and finishing rabbit - Kustos, Károly; Abayné Hamar, Enikő; Balláné Erdélyi, Márta; Fazekas, Natasa; Heincinger, Mónika; Kovács-Weber, Mária; Nyíri, András; Szabó, Rubina; Zimborán, Ágnes; Gerber, Zsuzsanna; Gerber, Johann; Somodi, Brigitta (Animal welfare, Ethology and Housing Systems (AWETH), 2016)
The health of rabbits is endangered by several reasons mostly during the post-separation period, which is most evident in the appearance of digestive disorders. These could be prevented by using antibiotic treatments as growth promoters, but because of their ban, alternative solutions are needed. In the experiments PreAcid BA® prebiotic acidification product (formic acid, lactic acid, gluconate, butyrate) was mixed in the feed mixture at a level of 0.2%. For the 5 to 11 weeks long fattening period, with 0.2% PreAcid BA® feed, there was no mortality at the first repetition (one rabbit/cage) of treated group, but in the other repetitions we detected the same or higher proportion of mortality, than the control groups’. There was no significant difference between the treated and the control groups in terms of live weight and slaughtered weight.